Sustainable Cryogenic Grinding Of AISI D2 Tool Steel Using Various Eco-Friendly Lubricants With MQL Technique - Sharma, Ashwani (IIT(BHU) Varanasi, 2023)
Abstract is available in the attachment.
Keywords: Mechanical Engineering